Efficacy of Resection of Lateral Wall of Endolymphatic Sac for Treatment of Meniere's Disease - Zhang, Daogong; Lv, Yafeng; Li, Xiaofei; Song, Yongdong; Kong, Ligang; Fan, Zhaomin; Wang, Haibo (Frontiers in Neurology, 2022)
Background To explore the long-term efficacy and safety of resection of the lateral wall of the endolymphatic sac for the treatment of intractable Meniere's disease (MD) as an alternative surgical procedure for treating this disorder. Methods Data from 73 patients who were referred to our hospital and diagnosed with unilateral MD between January 2015 and June 2019 were retrospectively analyzed in this study. Seventy-three patients who had frequent vertigo even after receiving standardized conservative treatment for at least half a year underwent resection of the lateral wall of the endolymphatic sac. Vertigo control and auditory function were assessed. Pure tone audiometry, caloric test, and vestibular evoked myogenic potential were performed to evaluate audiological and vestibular functions. The post-operative follow-up duration was more than 2 years. Results Among the 73 patients (male 34 cases, female 39 cases; age 20–69 years, average 51.4), vertigo was controlled effectively for 66 cases (90.4%) after 2 years of follow-up; 45 cases (61.6%) were completely controlled, and 21 cases (28.8%) were substantially controlled in this study. The patients of 16.4% had hearing loss with more than 10 dB change based on the four-tone average (0.5, 1, 2 and 3 kHz). No patient had a facial nerve weakness, cerebrospinal fluid leakage, or other complications. Conclusion Resection of the lateral wall of the endolymphatic sac, which can effectively control vertiginous symptoms in intractable MD patients, represents an effective and safe therapy for this disease. Resection of the lateral wall of the endolymphatic sac is expected to be used as an alternative treatment for MD.